Metaphorical Verbalization of the Concept 'Woman' in the Victorian Novels of Mary Braddon - Olena Novosadska (Linguaculture, 2020)
The representation of women in the written texts of the Victorian Era has received a great deal of attention and critics have analysed different strategies used for the description of women in novels. This paper looks at a particular device employed by the Victorian novelist Mary Braddon in the representation of women, namely, the use of conceptual metaphors. Women and metaphors alike are at once meditational and relational. A woman serves to mediate between man and man, man and Nature, man and Spirit. The research deals with repeated metaphors presenting women in the guise of foods, animals, babies, parts of the body, members of the aristocracy and supernatural creatures. Bearing in mind the social force of metaphor in our understanding of the world and of ourselves as well as the important role language plays as a channel through which ideas and beliefs are transmitted and perpetuated, the present study attempts to offer a preliminary exploration of how images of women are transmitted and perpetuated by the Victorian novelist Mary Braddon through linguistic metaphors.